Dinamika Gender dalam Islam : Perspektif Muslimah Terhadap Feminisme di Era Digital - Nabila, Nabila; Nur Alia Abdullah, Mirna; Retsa Rizaldi Mujayapura, Muhammad (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2025)
The issue of gender roles continues to develop along with the development of current technology. With the advancement of digital technology that is very significant, it provides a lot of space easily for everyone to build interactions with each other, one of which is a discussion about gender roles in Islam when associated with feminism. This provides Muslim women with an understanding of feminism that is very easy and fast. This study aims to examine how Muslim women's perspectives on current gender issues are when associated with feminism. This research was conducted using a qualitative method and interviews with Muslim women who are aware of issues regarding feminism with the help of literature studies as a data collection tool. The results of this study explain that feminism is a movement to defend and fight for women's rights. With this research, it can increase the insight of Muslim women in utilizing social media as a tool for open discussion with many people about gender equality.